The use of digital elevation models for detailed mapping of slope soils - Achasov, Andriy Borisovich; Achasova, Alla Oleksandrivna; Siedov, Arkadiy Oleksandrivich (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2019)
Formulation of the problem. The current stage of agricultural development in Ukraine requires highly informative soil maps.One of the directions for creating such maps is the use of digital elevation models (DEM) as a spatial translator of soil characteristics.The literary review has showed that despite the large volume of publications on this topic, a number of issues of soils digital mapping remain relevant.The purpose of the article is to study the possibilities of using relief-ground indicative models in creation of detailed digital ground maps.Methods. The research was conducted on the territory of the testing ground. During the field study of the landfill, it has been established that the soils are represented by chernozem typical of varying erosion degrees.It is proposed to use a xeromorphism coefficient for the quantitative account of the landforms influence on soil formation, characterizing changes in hydrothermal conditions for a particular section of the topography, compared with the horizontal surface.A detailed DTM was obtained, using the "Phantom 3" UAV.The derivative models of a number of topographic parameters were built on its basis later. A digital model of xeromorphism of the territory was built, transformed into a model of organic carbon (C) content.The specified map shows initial conditions of the soil cover. It can be used as a standard to compare parameters of modern soils for assessment of extent of their degradation.Comparison of this map with the map of actual C content has shown that average loss of C by soils of the studied area owing to anthropogenic degradation can be estimated at 5.1 kg on 1 t of the soil.Results. Investigations have proved that the geoinformation analysis of landforms allows to quantitatively shape hydrothermal conditions of soil formation for a certain territory. The cartographic materials constructed on such a methodical approach characterize landscape potential on soil formations and reflect quasi-virgin land condition of the soil.Scientific novelty and practical significance. The detailed soil maps, based on the results of field and laboratory soil studies, leading to potential soil assessment for DEM analysis in the article, allow to adequately estimate and objectively represent distribution of eroded and xeromorphic soils and their complexes on sloping lands.